2013
DOI: 10.1088/0953-8984/25/44/445011
|View full text |Cite
|
Sign up to set email alerts
|

Zero-temperature phase diagram of D2physisorbed on graphane

Abstract: We determined the zero-temperature phase diagram of D₂ physisorbed on graphane using the diffusion Monte Carlo method. The substrate used was C-graphane, an allotropic form of the compound that has been experimentally obtained through hydrogenation of graphene. We found that the ground state is the δ phase, a commensurate structure observed experimentally when D₂ is adsorbed on graphite, and not the registered √3 x √3 structure characteristic of H₂ on the same substrate.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Physisorption on PAHs can be directly considered, on the other hand, as a model to study hydrogen storage 16,17 . The characterization of phase diagrams and the heat capacity of systems formed by layers of H 2 on either graphite or graphene has been the goal of numerous investigations in the [18][19][20][21][22][23][24][25] . Attachment of H 2 and D 2 to fullerenes has been also experimentally investigated in comparison with some other physisorbed species such as rare gases (RG) or N 2 : The electronic absorption spectra recorded by Holt et al 26 revealed a marked influence of the corresponding ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Physisorption on PAHs can be directly considered, on the other hand, as a model to study hydrogen storage 16,17 . The characterization of phase diagrams and the heat capacity of systems formed by layers of H 2 on either graphite or graphene has been the goal of numerous investigations in the [18][19][20][21][22][23][24][25] . Attachment of H 2 and D 2 to fullerenes has been also experimentally investigated in comparison with some other physisorbed species such as rare gases (RG) or N 2 : The electronic absorption spectra recorded by Holt et al 26 revealed a marked influence of the corresponding ligand.…”
Section: Introductionmentioning
confidence: 99%